The blackening of organotin catalyzed silicone adhesive via low dose rate gamma irradiation - Bo Liu; Lei Yu; Yinyong Ao; Pucheng Wang; Wei Huang (Nuclear Analysis)
Low dose rate gamma irradiation blackening effect of organotin catalyzed silicone adhesive is presented. When the total dose accumulated to 350 kGy at low dose rate (0.03 Gy/s), there is a significant blackening of the color changing from transparent to black by the increasing of dose, which is simultaneously deepened by the decreasing of dose rate. That is, low dose rate and accumulated dose both affect the final color of silicone adhesive. The structure changes of silicone adhesive before and after blackening are characterized by UV–vis, FTIR, and SPME-GC-MS, and the mechanism of blackening is deduced to be related to the content of SnO.